2004
DOI: 10.1016/j.trstmh.2003.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Artemether in the treatment of falciparum malaria during pregnancy in eastern Sudan

Abstract: This study was carried in New Halfa Hospital, eastern Sudan from October 1997 to February 2001. Twenty-eight pregnant Sudanese women infected with Plasmodium falciparum were treated with intramuscular artemether (six injections, 480 mg) after failure of chloroquine and quinine therapy. The patients were followed-up until delivery; the babies were followed-up until the age of 1 year. Artemether was given to one patient in the tenth week of gestation, to 12 during the second trimester, and to 15 during the third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 18 publications
1
50
0
Order By: Relevance
“…This association needs to be confirmed in larger studies, particularly as we lack locus amplification data for posttreatment isolates. There is published evidence that injectable artemether monotherapy has been in use by medical practitioners in northern Sudan (1,10,21), and this may have led to selection of parasites carrying this gene amplification (15,31); no such amplification was observed among 24 isolates collected in 1989 (2). Continual surveillance of pfmdr1 and other loci implicated in antimalarial treatment response is justified as large-scale use of ACT continues in sub-Saharan Africa.…”
mentioning
confidence: 99%
“…This association needs to be confirmed in larger studies, particularly as we lack locus amplification data for posttreatment isolates. There is published evidence that injectable artemether monotherapy has been in use by medical practitioners in northern Sudan (1,10,21), and this may have led to selection of parasites carrying this gene amplification (15,31); no such amplification was observed among 24 isolates collected in 1989 (2). Continual surveillance of pfmdr1 and other loci implicated in antimalarial treatment response is justified as large-scale use of ACT continues in sub-Saharan Africa.…”
mentioning
confidence: 99%
“…However, an abortion was noted in two sheep 7 days following a single 40-and 160-mg/kg intramuscular dose of artemether. Several studies, which evaluated the safety of the artemisinins in pregnant malaria patients, found that birth outcomes did not differ significantly to community rates for abortion, stillbirth, or congenital abnormality (McGready et al 2001;Adam et al 2004;Clark et al 2004). For example, the overall abortion rate for women treated with artemisinins in Thailand during the first trimester was 18.9% compared to an overall community et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although quinine appears safe in early pregnancy (57,58), the efficacy of monotherapy in pregnancy is declining with some studies reporting failure rates of up to 35% (59) consistent with the slow but steady increase in reports of parasite resistance and associated molecular markers (60).…”
Section: First Trimestermentioning
confidence: 96%